Strengthening Sustainability in the Cement Industry - World Bank (World Bank, Washington, DC, 2022)
Concrete literally holds the modern world together. The material and its binding agent cement comprise a key ingredient in the buildings and roads essential for development and in infrastructure critical to sustainable growth. The cement industry also generates about seven percent of the world’s greenhouse gas emissions. While manufacturers have reduced emissions in recent decades, the industry must accelerate these efforts considerably if it is to meet its goal of achieving carbon-neutral concrete by 2050. Decarbonization by the cement industry will require collaboration with policy makers, financial institutions such as the International Finance Corporation (IFC), and end users in the built environment. The complex path to achieving net-zero manufacturing underscores the challenges facing high-emissions industries as they seek to reduce their carbon footprint and build a circular economy. IFC will complement the work of investors, regulators, and end-users to help forward-thinking and innovative players along the pathways leading towards a zero carbon future.